2007
DOI: 10.1063/1.2812573
|View full text |Cite
|
Sign up to set email alerts
|

Threshold voltage stability of organic field-effect transistors for various chemical species in the insulator surface

Abstract: Influence of fine roughness of insulator surface on threshold voltage stability of organic field-effect transistors Appl. Phys. Lett. 93, 033308 (2008); 10.1063/1.2957987 Effects of the permanent dipoles of self-assembled monolayer-treated insulator surfaces on the field-effect mobility of a pentacene thin-film transistor Appl. Phys. Lett. 90, 132104 (2007); 10.1063/1.2457776 Threshold voltage shift in organic field effect transistors by dipole monolayers on the gate insulator J. Appl. Phys. 96, 6431 (2004); 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 15 publications
(10 reference statements)
2
60
0
Order By: Relevance
“…In most studies, stress effects with SiO 2 gate dielectric are reduced when the substrate surface is rendered more hydrophobic through the use of SAMs. However, Suemori et al [36] found for bottom-gate, top-contact pentacene FET with a SiO 2 gate dielectric that SAM modification with long alkyl chains, such as octadecyl-or octyl-trichlorosilane, exhibits significantly more pronounced threshold-voltage shift under negative gatebias stress than SAMs with short alkyl chains. This was attributed to a lowering of the activation energy for trap creation.…”
Section: Role Of Extrinsic Factorsmentioning
confidence: 96%
“…In most studies, stress effects with SiO 2 gate dielectric are reduced when the substrate surface is rendered more hydrophobic through the use of SAMs. However, Suemori et al [36] found for bottom-gate, top-contact pentacene FET with a SiO 2 gate dielectric that SAM modification with long alkyl chains, such as octadecyl-or octyl-trichlorosilane, exhibits significantly more pronounced threshold-voltage shift under negative gatebias stress than SAMs with short alkyl chains. This was attributed to a lowering of the activation energy for trap creation.…”
Section: Role Of Extrinsic Factorsmentioning
confidence: 96%
“…Suemori et al reported a similar result for the pentacene transistor, where a longchain chemical species on the insulator surface increased the V T shift from ON gate bias stress. [ 63 ] They attributed this to the lowering of the activation energy for trap creation but the physical origin was not clear. It seems that V T shift is related to the roughness rather than the grain size.…”
Section: Threshold Voltage Shift From Gate Bias Stressmentioning
confidence: 98%
“…, hysteresis in drain current-gate voltage ( I D -V G ) curves [9][10][11][12][13] and V Ginduced threshold voltage ( V T ) shifts. [14][15][16] For the fabrication of OFETs by solution process, the polymer gate dielectrics which are not dissolved by liquid deposition of soluble organic semiconductors are essential. Therefore, thermally curable polymer gate dielectrics such as poly(vinyl phenol) (PVP) [ 12 , 13 , 17 , 18 ] and polyimide [ 18 , 19 ] are expected to be promising candidates for this process.…”
Section: Doi: 101002/adma201001871mentioning
confidence: 99%